Open-label uncontrolled pilot study on antipsoriatic activity of Rosa hemisphaerica - Adham, Aveen N.; Muttalib, Lana Y.; Naqishbandi, Alaadin M.; Ali, Salah Abu Baker (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Rosa hemisphearica (Rosaceae) is highly cultivated worldwide as an ornamental plant and medicinally have an antibacterial and antioxidant effect. This study aimed to investigate clinically and histopathologically the anti-inflammatory activity of Rosa hemisphearica in psoriasis and to correlate the anti-inflammatory activity with the active constituents in the plant by the phytochemical study. Methods: In this open-label uncontrolled pilot study, a topical preparation of R. hemisphearica stem extract was used by 20 patients suffering from psoriasis for three weeks. Three histopathological slides for each patient, one each week for three weeks was done for anti-inflammatory response evaluation. Subsequently, total phenolic content was measured followed by thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC) analysis for the identification of phenolic acid content in the stem. Results: By histopathological examination revealed that both Munro’s and Kogoj’s abscesses were gradually disappeared, the granular layer gradually restored to normal and the inflammatory cells gradually reduced in number prominently polymorph (neutrophils) and eventually histocytes disappeared. Total phenolic contents in R. hemisphearica stem extract were determined as 205.625 µg gallic acid equivalent each gm of the sample extract, TLC, and HPLC results showed the presence of rosmarinic acid in the stem extract. On quantitative HPLC analysis, the percentage of rosmarinic acid in the stem extract was 0.024 with a retention time (Rt) of 3.4 min. The proposed HPLC method was found to be linear, accurate and precise. Conclusion: The organic solvent extract of R. hemisphearica stem showed a significant reduction in an inflammatory cell among psoriatic patients under study. Rosmarinic acid was identified by TLC and HPLC as important phenolic acid constituents.